ANALISIS PENGARUH GAYA HIDUP HEDONIS, LITERASI KEUANGAN ISLAM, DAN LINGKUNGAN SOSIAL TERHADAP PERILAKU KONSUMTIF MAHASISWA EKONOMI ISLAM FEB UNDIP - Vivi claudiana; Nenik Woyanti (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2026)
More university students are showing a tendency to spend money freely as digital culture continues to develop, social media, and social environmental pressures indicates a gap between their educational background in Islamic economics and the consumption practices applied in daily life. This research looks into how a hedonistic lifestyle, knowledge about Islamic finance, and the social surroundings influence the spending habits of undergraduate students in the Islamic Economics Study Program at the Faculty of Economics and Business, Diponegoro University. This research employs a quantitative approach using a survey method by distributing questionnaires to students enrolled during the 2021–2024 academic years. The sample was determined using purposive random sampling, and the data were analyzed using multiple linear regression techniques with SPSS software. The findings indicate that a hedonistic lifestyle and the social environment have a positive and significant partial effect on students’ consumptive behavior, while Islamic financial literacy has a negative but insignificant effect on consumptive behavior. Meanwhile, hedonistic lifestyle, Islamic financial literacy, and the social environment simultaneously have a significant effect on students’ consumptive behavior. These findings suggest that social pressure and lifestyle tendencies are dominant factors in shaping students’ consumptive behavior, despite their background in Islamic economics education. Keywords: Hedonistic Lifestyle; Islamic Financial Literacy; Social Environment; Consumptive Behavior;